Governance and scope economies in Microfinance Institutions. (2013) - Hartarska, Valentina; Mersland, Roy; Nadolnyak, Denis; Parmeter, Christopher
This paper studies the relation between board size and composition and cost savings (scope economies) from combining savings mobilisation and lending by Microfinance Institutions (MFIs). The findings support the hypothesis that employee representation on the board is associated with positive scope economies, possibly due to internal knowledge. However, CEO-Chairman duality is associated with equal or larger probability of scope diseconomies, which is consistent with previous findings. Representation of other stakeholders on the MFI board does not affect scope economies. The results seem to support the notion that, in highly uncertain environments, group cohesion may be an advantageous mechanism of control.